2018
DOI: 10.1161/circep.117.005250
|View full text |Cite
|
Sign up to set email alerts
|

Ten-Year Clinical Outcome After Circumferential Pulmonary Vein Isolation Utilizing the Hamburg Approach in Patients With Symptomatic Drug-Refractory Paroxysmal Atrial Fibrillation

Abstract: Ten-year single-procedural outcome of CPVI in patients with paroxysmal atrial fibrillation resulted in stable sinus rhythm in 32.9% and in 62.7% of patients after multiple procedures. The progression rate to persistent AF was remarkably low.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
43
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(45 citation statements)
references
References 21 publications
1
43
0
1
Order By: Relevance
“…The predictive value of AF history duration on AF recurrence remains controversial because the duration of a patient's AF history may not always be equivalent to the actual length of the AF episodes, and hence, may not reflect disease severity such as atrial remodeling. No association between AF clinical history duration prior to radiofrequency ablation and recurrence rate has been reported in previous series 7,9,10 evaluating the very long-term (more than 10 years) success of pulmonary veins isolation, nor in the surgical experience described in the Atrial Fibrillation Ablation and Autonomic Modulation via Thoracoscopic Surgery (AFACT) study. 8 On the other hand the duration of AF history, number of antiarrhythmic drugs, and left atrial diameter indexed by the body surface area were significant predictors of AF-recurrence in a Takigawa et al series 4 who studied, in 1220 paroxysmal AF patients, the incidence of AF recurrence and progression from paroxysmal to persistent AF, after catheter ablation.…”
Section: Af History and Catheter Ablation Outcomementioning
confidence: 98%
See 1 more Smart Citation
“…The predictive value of AF history duration on AF recurrence remains controversial because the duration of a patient's AF history may not always be equivalent to the actual length of the AF episodes, and hence, may not reflect disease severity such as atrial remodeling. No association between AF clinical history duration prior to radiofrequency ablation and recurrence rate has been reported in previous series 7,9,10 evaluating the very long-term (more than 10 years) success of pulmonary veins isolation, nor in the surgical experience described in the Atrial Fibrillation Ablation and Autonomic Modulation via Thoracoscopic Surgery (AFACT) study. 8 On the other hand the duration of AF history, number of antiarrhythmic drugs, and left atrial diameter indexed by the body surface area were significant predictors of AF-recurrence in a Takigawa et al series 4 who studied, in 1220 paroxysmal AF patients, the incidence of AF recurrence and progression from paroxysmal to persistent AF, after catheter ablation.…”
Section: Af History and Catheter Ablation Outcomementioning
confidence: 98%
“…Some studies found a statistically significant independent association between AF history duration prior to radiofrequency ablation and recurrence after the procedure, [2][3][4][5] whereas this relationship has not been reported in other series. [6][7][8][9][10] Clarification of this issue might have important implications since there seem to be a tendency to postpone catheter ablation in patients with a short clinical history of AF. 1 The aim of our study is to investigate the impact of length of time elapsing from AF diagnosis on 1-year outcome of AF catheter ablation in a large cohort of patients enrolled in the Atrial Fibrillation Ablation Long-Term Registry, 11 initiated by the European Heart Rhythm Association, conducted by the EURObservational Research Programme (EORP) of the European Society of Cardiology (ESC).…”
Section: Introductionmentioning
confidence: 99%
“…When compared with antiarrhythmic drugs (AADs), catheter ablation has shown superior rhythm control strategy for paroxysmal AF even as first‐line treatment . However, stable sinus rhythm cannot be maintained by PVI alone in some paroxysmal AF and in the majority of persistent or longstanding persistent AF …”
Section: Introductionmentioning
confidence: 99%
“…Antiarrhythmic drugs, such as amiodarone, should be stopped for at least five half‐lives long before the surgery. After the 8‐h fasting, CPVI was performed for all patients, as previously described . Ablation was performed briefly under general anesthesia with the administration of midazolam and fentanyl citrate.…”
Section: Methodsmentioning
confidence: 99%
“…Atrial fibrillation (AF) is one of the most common clinical arrhythmias affecting about 1.5‐2% of the general population in developed countries . Several complications, including congestive heart failure, stroke, and hospitalization, were associated with AF .…”
Section: Introductionmentioning
confidence: 99%